PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI DI SMK IBRAHIMY 1 SUKOREJO MENGGUNAKAN KERANGKA KERJA TOGAF ADM - Akhlis Munazilin; Alifia Rosa Fridausiah; Ishqy Bela (Jurnal Riset Teknik Komputer, 2026)
The development of information technology demands that educational institutions have an integrated and efficient information system. SMK Ibrahimy 1 Sukorejo requires an information system enterprise architecture design that can align business and technology needs. This study uses the TOGAF ADM framework as a design method, which includes the preliminary phase, architecture vision, business architecture, information system architecture, technology architecture, and migration planning. The result is an enterprise architecture blueprint that covers business, data, application, and technology aspects. This architecture is expected to improve data management efficiency, accelerate administrative processes, and support digital learning that is adaptive to technological developments. By implementing TOGAF ADM, SMK Ibrahimy 1 Sukorejo can develop a structured and sustainable information system, supporting the institution's vision and mission in the digital era.